Formulasi Antioksidan Minyak Daun Lemo (Litsea cubeba Pers.) Dengan Oleum Olivarum Sebagai Pelarut - Ana Yulyana; Satrio Satrio Ari Hutomo; Munawarohthus Sholikha (Universitas Muhammadiyah Pekajangan Pekalongan, 2024)
Litsea cubeba, also known as lemo, is a plant rich in antioxidant compounds and has been used in various studies to explore its potential in protecting the skin from oxidative damage. Recent research indicates that Litsea cubeba leaf oil possesses significant antioxidant activity, measured using the DPPH method, demonstrating its capacity to counteract free radicals. Additionally, this oil also contains vitamin E, known for its antioxidant properties, with measurable levels found in the studies. The physical stability of the lemo leaf oil formulation has also been evaluated, showing no change in shape or smell after a 14-day cycling test, indicating good potential for long-term application. These results affirm that Litsea cubeba holds great promise as a raw material in skincare products, particularly as an antioxidant, which can help protect the skin from the negative effects of free radicals and oxidation processes.